CagA and VacA genes of Helicobacter pylori and their clinical relevance - Lavanya Jeyamani; Jayalakshmi Jayarajan; Venkatakrishnan Leelakrishnan; Mukundan Swaminathan (Wolters Kluwer Medknow Publications, 2018)
Context: Helicobacter pylori is associated with the development of a variety of gastroduodenal diseases which varies with ethnicity and the type of strains that infect the population. Aims: This study aims to evaluate the prevalence of H. pylori cagA and vacA genotypes in our region and to determine their relationship to the severity of the lesions that they cause. Settings and Design: This study was an observational cross-sectional study. Subjects and Methods: DNA was extracted from 165 gastric biopsies from patients evaluated for dyspepsia. PCR was used to detect cagA and vacA (s1, s2, m1, m2) genes of H. pylori. Statistical analysis of associations was performed between endoscopy findings and virulence genes. Statistical Analysis Used: Pearson Chi-square test and Fischer's exact test. Results: The prevalence of H. pylori infection was 37% and the dominant genotypes was vacA s1 cagA-positive strain (54.1%) in this study. The vacAs1 subtype was found in all patients with peptic ulcer disease (PUD). The entire normal study group had VacA s2 variant only. This clearly shows that vacA s1 is a significant virulence marker and patients harboring s1 strains are more prone to develop ulcers (P = 0.007). There was a significant association of cagA with s1 strain rather than s2. Variation in VacA m genotype did not seem to have any association with disease status. There was a statistically significant association between the presence of cagA gene and PUD rather than the nonulcer dyspepsia (P = 0.027). Conclusion: The predominant genotype in our population was cagA positive vacA s1, which was found to be significantly associated with patients with gastric diseases, especially PUD. VacA s1 can serve as a single best virulence marker of the disease manifestation.